Numerical thermal analysis of synchronous reluctance generator for wind energy application - Tefera Kitaba Tolesa; Praveen Tripathy; Ravindranath Adda (Energy Conversion and Economics)
Abstract This paper focuses on the thermal analysis of the synchronous reluctance generator with a rating of 2.1 kW. It mainly uses explicit, and implicit finite difference methods for thermal analysis to reduce the complexity of thermal calculation for the machine's components. It compares the results with the results obtained using a finite element analysis (FEA) and includes the experimental verification of the obtained results. The explicit, and implicit finite difference thermal analysis is relatively simple and computationally fast. Once the design parameters are known, the electric losses and iron losses of the synchronous reluctance generator are evaluated. These machine parameters are utilized in developing the explicit finite difference (EFD), an implicit finite difference (IFD), and a 3D FEA model for thermal analysis. It is observed that the obtained results from the EFD, IFD, FEA, and experiments are very close to each other, and the temperature rise for the designed machine is within the desired and acceptable range.